Performance Strategy to Improve Quality for Hotel Employees Post Covid-19 at Conrad Hotel Nusa Dua BALI - Raditya, Putu Tiana; Artha Putra, I Nengah Sandi; Nita Kristiana, Komang Shintiya (Akademi Komunitas MAPINDO, 2024)
The purpose of this research is to determine strategies for the quality of employee performance and hoteldevelopment after Covid 19 to improve the quality and standards of guest comfort. Various hotel sectors in theNusa Dua area are competing with each other to improve and renovate everything that is still lacking andmaximize it for the comfort of guests visiting the hotel. the hotel and in general to increase the hotel's incomeand of course also have a big impact on the attractiveness of tourists who visit the hotel. The Covid-19 pandemichas become a global problem that has not only hit the health sector but also Bali tourism in particular. Thedecline in the tourism sector is demonstrated by the decrease in the number of room occupants and the averagelength of stay of guests at each hotel in Nusa Dua. This decline meant that hotel revenues were greatly reducedand they had to bear high operational costs. So, a quality strategy for employee performance is needed forhotels in Nusa Dua, especially at the Conrad Bali Hotel, in preparing work guidelines for the progress andcontinued comfort of guests staying at the hotel. By using interview analysis of one of the employees at theConrad Hotel Nusa Dua, Bali, the results were found to be the best quality strategy for employee performance.For example, creating and rearranging guidelines or procedures to increase the level of standardization andquality of work for every employee who works at the Conrad Hotel Nusa Dua. And supported by the use of theentire tourism workforce to seize and take advantage of maximum opportunities. Such as supporting nationalto international scale activities carried out in Nusa Dua, Bali. Some of the suggestions given to support thisresearch are that hotels in Nusa Dua, Bali in particular must be more active in carrying out various promotions,either through online promotions, through online travel agents, social media or through tourism organizations such as through the tourism office. Bali, influencers and the central government are still supported by CHSEcertificates and maintaining health protocols during the pandemic to maintain the safety of tourists visitingand staying in Nusa Dua, Bali. Apart from that, during the pandemic period where we don't know how long itwill end, hotels can collaborate with local governments to intensify promotions to friendly countries which canincrease foreign exchange sources and regional income, for example Chinese and Russian tourists.Keywords: Employee quality, work strategy, tourism development.